Episcopacy and Reform in England in the Later Sixteenth Century - Collinson, Patrick (Studies in church history, 1966)
On the second day of the Hampton Court Conference of January 1604, King James I rebuked Dr John Reynolds of Oxford in words which are almost painfully familiar. A Scottish presbytery, pronounced the royal theologian, ‘as well agreeth with a monarchy as God and the Devil,’ and there followed what a Scot later remembered as ‘that unkoth motto,’‘no bishop, no king.’ The king’s bon mot so perfectly epitomises an important principle of Stuart policy that it may seem an act of pedantry to ask whether in fact the proposals which provoked it included the extirpation of bishops. But Dr Barlow, author of the Summe and substance of the conference, seems to have appreciated that Reynolds had spoken of no such thing. The king was ‘somewhat stirred,’ he explains, ‘thinking that they aymed at a Scotish presbytery.’